Effect of black cumin oil (Nigella sativa L.) on fresh fish (Barbus grypus) fillets during storage at 2 ± 1 °C - Ozpolat, Emine; Duman, Muhsine (Soc Brasileira Ciencia Tecnologia Alimentos, 2017)
It is important that the methods and materials used for to lengthen the shelf-life of food are simple, inexpensive and safe. For these reasons, herbal additives like cumin oil (Nigella sativa L.) have been preferred recently. Thus, the present study focuses on the influence of black cumin oil on chemical, microbiological and sensory quality of fish (Barbus grypus) fillets during storage at 2 +/- 1 degrees C. Acceptability scores for sensory quality of all described treatment groups decreased with storage time. Defined limits for mesophilic bacteria and Total volatile basic nitrogen (TVB-N) were reached after 21st days for the control group, after 24th days for with 0.2% black cumin oil treated group and after 28th days for with 0.4% and 0.6% black cumin oil treated groups. No difference was found among groups during storage in terms of defined thiobarbituric acid (TBA) values. Consequently, it was found that black cumin oil treated groups had longer shelf-life and higher sensory quality than the untreated control group.
Keywords: black cumin oil; Barbus grypus; Nigella sativa; shelf life